Kebiasaan sarapan dan status gizi pelajar SMP - Makanoneng, Gwyneth Gwendellyn; Musa, Ester Candrawati; Sanggelorang, Yulianty (Holistik Jurnal Kesehatan, 2025)
Background: According to the Global Nutrition Report, rates of malnutrition among adolescents have declined, but cases of obesity and overweight have increased significantly. In 2019, an estimated 15.1% of adolescents were obese, while 5.7% were classified as underweight. This situation creates a nutritional problem known as the "triple burden of malnutrition," a combination of undernutrition, overweight, and micronutrient deficiencies. Breakfast habits are one factor influencing nutritional status. Purpose: To determine the relationship between breakfast habits and nutritional status in junior high school students. Method: This quantitative, observational, and analytical study used a cross-sectional study design conducted at Pineleng 2 Public Junior High School, Minahasa Regency, involving 77 respondents. The variables in this study were breakfast habits and nutritional status. Data were collected through anthropometric measurements (weight and height) to determine BMI/A, followed by Z-scores and a non-sequential 2x24-hour breakfast habits and food recall questionnaire. Data analysis was performed univariately and bivariately using Fisher's exact test through the Statistical Program for Social Sciences to see the relationship between variables. Results: The majority of respondents (75.3%) had normal nutritional status, while 24.7% were categorized as abnormal (underweight, overweight, or obese). Ninety-four percent of students had frequent breakfast habits (≥4 times/week), and 5.2% had infrequent breakfast habits (<4 times/week). Students with good breakfast habits were mostly those with normal nutritional status (p=0.044) (p<0.05). Conclusion: There is a relationship between breakfast habits and nutritional status. Good breakfast habits are a determining factor in students' nutritional status. Regular and nutritious breakfasts help meet daily nutritional needs while maintaining ideal nutritional status according to body mass index and age. In addition to breakfast habits, other important factors influencing nutritional status include a balanced diet and general health. Suggestion: Future researchers are encouraged to conduct research on the factors influencing breakfast habits, macronutrient intake, and nutritional status of school students.   Keywords: Breakfast Habits; Lessons; Nutritional Status.   Pendahuluan: Berdasarkan laporan Global Nutrition Report, angka kekurangan gizi pada remaja memang menurun, tetapi kasus obesitas dan kelebihan berat badan justru mengalami kenaikan yang cukup signifikan. Pada tahun 2019, diperkirakan 15.1% remaja mengalami obesitas, sedangkan 5.7% tergolong kekurangan berat badan. Kondisi ini menimbulkan masalah gizi yang disebut "triple burden of malnutrition", yaitu kombinasi antara kurang gizi, kelebihan berat badan, dan defisiensi mikronutrien. Kebiasaan sarapan merupakan salah satu faktor yang memengaruhi status gizi. Tujuan: Untuk mengetahui hubungan antara kebiasaan sarapan dengan status gizi pada pelajar SMP. Metode: Penelitian kuantitaif yang bersifat observasional analitik dengan menggunakan desain atau rancangan cross sectional study yang dilaksanakan di SMP Negeri 2 Pineleng, Kabupaten Minahasa dengan melibatkan 77 responden. Variabel dalam penelitian ini adalah kebiasaan sarapan dan status gizi. Data dikumpulkan melalui pengukuran antropometri (berat badan dan tinggi badan) untuk mengetahui IMT/U, dilanjutkan dengan Z-score serta kuesioner kebiasaan sarapan dan food recall 2x24 jam secara tidak berurutan. Analisis data dilakukan secara univariat dan bivariat dengan uji Fisher’s exact test melalui program Statistical Program for Social Sciences untuk melihat hubungan antara variabel. Hasil: Sebagian besar responden 75.3% memiliki status gizi normal, sementara 24.7% termasuk dalam kategori tidak normal (kurus, gemuk, atau obesitas). Sebanyak 94.8% siswa memiliki kebiasaan sarapan yang sering (≥4 kali/minggu), dan sebanyak 5.2% siswa memiliki kebiasaan sarapan yang jarang (<4 kali/minggu). Siswa yang memiliki kebiasaan sarapan yang baik didominasi dengan status gizi normal (p=0.044) (p<0.05). Simpulan: Terdapat hubungan antara kebiasaan sarapan dengan status gizi. Kebiasaan sarapan yang baik merupakan salah satu faktor penentu status gizi siswa. Sarapan yang teratur dan bergizi membantu memenuhi kebutuhan nutrisi harian sekaligus mempertahankan status gizi ideal sesuai indeks massa tubuh dan kategori usia. Selain kebiasaan sarapan, faktor penting lain yang turut memengaruhi status gizi meliputi pola makan seimbang dan kondisi kesehatan secara umum. Saran: Bagi peneliti selanjutnya diharapkan dapat melakukan penelitian terkait tentang faktor-faktor yang mempengaruhi kebiasaan sarapan pagi, asupan zat gizi makronutrien dan status gizi siswa di sekolah.   Kata Kunci: Kebiasaan Sarapan; Pelajaran; Status Gizi.